Free-standing, anti-corrosion, super flexible graphene oxide/silver nanowire thin films for ultra-wideband electromagnetic interference shielding - Jia, Hui; Yang, Xiao; Kong, Qing-Qiang; Xie, Li-Jing; Guo, Quan-Gui; Song, Ge; Liang, Lei-Lei; Chen, Jing-Peng; Li, Yan; Chen, Cheng-Meng (Journal of materials chemistry. A, Materials for energy and sustainability, 2021)
The exploration of ultra-wideband electromagnetic shielding materials is still a huge challenge in the elimination of electromagnetic interference from electronic devices of various frequencies in military and civil fields. Herein, a free-standing graphene oxide/silver nanowire (GO/Ag-7L) film with a dense sandwich-like structure is fabricated via vacuum-assisted self-assembly. Compared with the random distribution of physical mixed films, silver nanowires are woven into a 3D conductive network in the multilayer GO/Ag-7L film, which provides a superb electrical conductivity (2255.8 S cm −1 ). Benefitting from the multilayer structure with multiple absorptions of the GO layer and multiple reflections of the silver nanowire network, the electromagnetic interference shielding effectiveness (EMI SE) is up to 62 dB when the thickness is merely 8 μm in the ultra-wideband of 8-40 GHz (covering the X-band, Ku-band, K-band, and Ka-band). The corresponding specific SE (EMI SE/ t ) is as high as 77 500 dB cm −1 . After inserting the GO layer, the GO/Ag-7L film exhibits outstanding flexibility and anti-corrosion properties. Considering practical application, it can be employed as a novel strain sensor with high sensitivity and a quick strain response in the robotics field, which satisfies the requirement for both electromagnetic interference protection and real-time motion monitoring. Thus, it has promising potential applications in sophisticated electronic equipment. A free-standing graphene oxide/Ag nanowire film with a dense sandwich-like structure was fabricated via vacuum-assisted self-assembly. The EMI SE is up to 62 dB when the thickness is merely 8 μm in 8-40 GHz. The corresponding specific SE (EMI SE/t) is up to 77 500 dB cm −1 .